1995
DOI: 10.1007/bf00005910
|View full text |Cite
|
Sign up to set email alerts
|

Ecomorphology of retinal structures in zooplanktivorous haplochromine cichlids (Pisces) from Lake Victoria

Abstract: SynopsisBefore the decline of the species flock of haplochromine cichlids of Lake Victoria due to the Nile perch upsurge, there were many co-existing haplochromine species such as the taxonomically and ecologically wellstudied zooplanktivores of the Mwanza Gulf . In spite of the scarcely separated niches of some of these species, no sign of competition for space or food could be demonstrated . As is argued in this paper, optical differentiation could well be an aspect of adaptive radiation of these, zooplankti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Witte 1984b, Goldschmidt et al 1990), morphology (e.g. van der Meer and Bowmaker 1995, van der Meer et al 1995), behavioral biology (Smith and Wooton 1994) and physiology (Rosenberger and Chapman 2000, Melnychuk and Chapman 2002). The second species, which closely resembles Haplochromis “argens,” was nicknamed Haplochromis “dusky argens”.…”
Section: Introductionmentioning
confidence: 99%
“…Witte 1984b, Goldschmidt et al 1990), morphology (e.g. van der Meer and Bowmaker 1995, van der Meer et al 1995), behavioral biology (Smith and Wooton 1994) and physiology (Rosenberger and Chapman 2000, Melnychuk and Chapman 2002). The second species, which closely resembles Haplochromis “argens,” was nicknamed Haplochromis “dusky argens”.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the reduced eye size found in the modern population of H. pyrrhocephalus was unexpected in relation to the assumed visual demands. Studies of the retina of H. pyrrhocephalus from before the environmental changes (old populations) revealed exceptionally large long‐wavelength‐sensitive (LWS) double cones (Van der Meer, Anker & Barel, 1995). In addition, Van der Meer & Bowmaker (1995) showed that the spectral sensitivity of this species covered significantly longer wavelengths compared to other haplochromines investigated.…”
Section: Introductionmentioning
confidence: 85%
“…There is some discrepancy regarding the double cone size of the old H. pyrrhocephalus population from the present study, and that of the sample used by Van der Meer et al . (1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations